A Content Analysis of Students - Yuliana, Nur Melani; Widiastuty, Hesty (Journal Of Foreign Language Learning and Teaching, 2022)
A factor that has an impact on the teaching and learning process is the instructional material. This means that input has typically always been provided by material creators in line with their understanding of how language may be effectively learned through input. This study attempts to determine how well the English textbook "Bahasa Inggris Kelas XII SMA/MA/SMK/MAK Edisi Revisi 2018" satisfies the standards for a good textbook proposed by Tomlinson. In this study, data were gathered using a descriptive methodology from two chapters of the textbook "Bahasa Inggris Kelas XII SMA/MA/SMK/MAK Edisi Revisi 2018". Based on the study, fourteen of the sixteen criteria of Tomlinson's theory for a good textbook were perfectly fulfilled, and the textbook failed to fulfill two of the requirements since it had some extraneous elements. The material of "Bahasa Inggris Kelas XII SMA/MA/SMK/MAK Edisi Revisi 2018" is mostly linked to Tomlinson's criteria for a good textbook. This textbook can be used as a reference for teaching and learning support in collaboration with another textbook, allowing the teacher to provide additional supporting materials and students with a choice of materials on relevant topics.